Harmonic and reactive power compensation as ancillary services in inverter-based distributed generation - Prodanovic,M; De,Brabandere K; Van,den Keybus J; Green,TC; Driesn,J (IET - Generation, Transmission and Distribution, 2007)
The introduction of distributed generation, DG, into low-voltage (LV) networks opens up the possibility of supplying ancillary services to aid network management and to maintain powerquality. DG itself can cause voltage magnitude difficulties when injecting real power into networks with high R/X ratios, but control of reactive power injection can help overcome this. Continuous control and support only at the voltage limit conditions (to avoid unnecessary reactive power flows in normal conditions) are explored. Relatively high-impedance LV networks are prone to harmonic distortion from nonlinear loads. A variety of control methods that emphasise either harmonic-line flows or local-voltage distortion are examined, and a compromise method based on resistance emulation is shown to be effective. Experimental results from a single-phase laboratory network and 2 kVA inverter are used to illustrate how these additional control functions can be integrated into the existing control scheme for real-power management. Decomposition of observed voltages and currents into harmonic terms that are phase synchronised to the grid voltage is a challenge in real-time systems. Kalman observers are used to achieve this with an additional advantage of avoiding explicit phase-locking while producing quadrature components useful in instantaneous calculation of reactive power and in providing feed-forward compensation terms.